Analysis of Healthy Housing and TB Prevalence in Yogyakarta City - Musfirah, Musfirah; Nurfita, Desi; Rangkuti, Ahmad Faizal (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Environmental health is one of the determinants factors toward the public health status. Transmission of tuberculosis (TB) is influenced by environmental factors. Based on previous TB data in local study, it shows that urban areas (urban) have a high case rate. Therefore, this study aims to reveal the disparity of urban TB sufferers, especially in the city of Yogyakarta based on indicators of the physical environment of the house from the coverage of healthy households. The method of study used is quantitative descriptive analysis of secondary data. The data used were the physical environment of the house which is obtained from healthy housing data and TB prevalence data in Yogyakarta City. The secondary data spread over 18 Public Health Centers in Yogyakarta City. The data collected include healthy housing data and BTA (+) cases data in the study scope using total sampling technique. Based on the trend analysis, it was found that there was a significant trend in data. The higher percentage of non-healthy housing coverage wasassociated in line with the higher the TB prevalence rate. It can be concluded that the physical environment factor of the house as an indicator of a healthy housing is closely related to the incidence of TB in Yogyakarta City. Environmental quality studies need to be carried out for comprehensive TB disease control towards elimination (End TB 2030) which is in line with national programs and SDGs goals.